Investigation of antimicrobial potencies of mixed-ligand complexes of divalent metal ions with Barbituric acid and 2,2-Bipyridine - Oluwabiyi J. Olaoye; Mary A. Oladipo; Kayode T. Ishola; Omobola A. Odedokun; Olayinka G. Ogunlade (International Research Journal of Science, Technology, Education, and Management)
The development of resistance by many pathogenic microorganisms towards many conventional antibiotic drugs has now become one of the major worldwide health challenges, which requires a search for more effective drugs to combat the growing threat of widespread antibiotic resistance. Therefore, in an attempt to search for new and effective antibiotic drugs, antimicrobial potencies of mixed ligand complexes of Cu (II), Co (II), Ni (II) involving barbituric acid and 2,2-bipyridine chelating agents were examined. The mixed-ligand complexes were synthesized and the formation of the complexes was established using elemental analysis, metal analysis, melting points, solubility test, infra-red and Uv-visible analysis. The complexes were investigated for their pharmaceutical exploits against bacteria (Bacillus substilis and Staphylococcus aureus, Pseudomonas aeruginosa and Clostridium spp.) and four fungi (Aspergillus flavus, Aspergillus niger, Saccharomyces cerevisiae and Candida albican). Three conventional antibiotic drugs were employed as reference drugs. The formation of the metal complexes in ratio 1:1:1 and molecular formulas were confirmed via elemental and metal analyses. The purity of the metal complexes was ascertained by the sharp melting points. Infrared spectroscopic analysis revealed the formation of coordination bonds between the ligands and the metal ions through nitrogen and oxygen donors. The formation of the metal complexes was substantiated by UV-visible electronic transitions. The diversity of antimicrobial activities was displayed by the metal complexes against the pathogenic organisms at inhibitory zones of 6 mm – 25 mm. The metal complexes produced more significant antimicrobial activity than the standard drugs and succeeded where the standard drugs failed. The complexes could be considered potential antimicrobial agents to replace the less effective conventional antibiotic drugs. The toxicity of the metal complexes should be evaluated to establish their suitability for replacement.